Recent Publications (Quarterly Journal of Economics, 1960)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 74, Issue 1, February 1960, Pages 163–166, https://doi.org/10.1093/qje/74.1.163 Published: 01 February 1960